O canteiro autogerido entre a experiência coletiva e a vida cotidiana: Empreendimentos José Maria Amaral e Florestan Fernandes - Aguiar, Renata Miron de (2021)
The capitalist logic structures the construction of cities, based on housing conceived as a commodity. In the context of the Minha Casa Minha VidaEntidades program, one can observe the struggle of social movements that seek to oppose the dominant logic, in the dispute for public funds and housing policies in the defense of rights through emancipatory processes, especially in the city of São Paulo. The objective of the research is to understand, under the precept of self-management in housing production, the organization and relationships experienced in the self-managed construction site. Through a qualitative study on the experiences of the housing projects José Maria Amaral and Florestan Fernandes, documentary research and interviews were carried out with subjectsvolunteers, technicians and leaders-with different skills, united by cooperative work, resulting in a critical analysis of the potential and limits of this collective practice. Thus, the importance of the political situation in interpersonal and bureaucratic relations that mediate relations in self-managed construction sites is recognized, in order to develop strategies for subversion of capitalist relations by the working class in the planning and construction of cities